Doxorubicin-induced cardiotoxicity: An update on the molecular mechanism, biomarkers and management - Amaan, Mohd; Goel, Radha; Paul, Surovi; Danish, Iqbal (Journal of Applied Pharmaceutical Research, 2024)
Background: Doxorubicin (DOX) is a widely used chemotherapeutic agent that is effective against various solid tumors and hematologic malignancies. However, its clinical application is severely limited by dose-dependent cardiotoxicity, which affects nearly 26% of patients. Objective: This review focuses on recent insights into the molecular mechanisms of DOX-induced cardiotoxicity, particularly highlighting the roles of oxidative stress and mitochondrial dysfunction. Methods: We have reviewed and retrieved the relevant information by probing the main keywords in online databases (PubMed, Scopus, Science Direct and Web of Science, etc.). Screening of relevant literature was done to pick suitable content based on the pharmacological profile of DOX. Key biomarkers such as troponins, brain natriuretic peptides (BNP), and atrial natriuretic peptides (ANP) are crucial for early detection of cardiac injury. The overproduction of reactive oxygen species (ROS) and reactive nitrogen species (RNS), mediated by enzymes like NADPH oxidase and mitochondrial cytochrome c, is central in triggering apoptosis and cardiomyocyte damage. Furthermore, DOX’s impact extends to other organs, notably the liver and kidneys, contributing to systemic toxicity. Conclusion: This review synthesizes current strategies to mitigate DOX-induced cardiotoxicity, including applying antioxidants, liposomal DOX formulations, and emerging nanocarrier technologies designed to enhance therapeutic selectivity. Looking ahead, integrating personalized medicine approaches and developing innovative therapeutic interventions hold promise for balancing DOX's antitumor efficacy with a reduced risk of cardiotoxicity. By addressing critical gaps in our understanding, this review highlights the need for integrative approaches combining biomarker discovery and targeted therapies to optimize patient outcomes and guide future research directions.